Key points of cooperation for successful implementation of bedside TCD in brain death determination - Xu, Guixing; Liu, Dawei; Xiao, Fang; Zheng, Donghua (International Journal of Advances in Medicine, 2020)
Background: To clarify the key points of cooperation in bedside TCD examination of potential brain death patients and ensure the successful implementation of bedside TCD. Methods: From June 2018 to May 2019, the clinical data of potential brain death patients, admitted in ICU of the First Affiliated Hospital of Sun Yat-sen University, were prospectively collected; for patients undergoing bedside TCD examination, through cooperating with TCD examination doctors, the related key points were summarized and analyzed. Results: Among 127 patients entered the study, including 103 males and 24 females, mean age is (33.2±15.2) years. 112 cases (88.2%) successfully implemented bedside TCD, 15 cases (11.8%) failed to implement bedside TCD. Univariate and multivariate analysis showed that: reasonable blood pressure regulation (systolic pressure: 90-140mmhg) (or = 6.58, 95% CI: 1.72-31.69), effective CCA compression test (rapid and accurate compression) (or = 13.62, 95% CI: 3.04-78.93) and body position adjustment (back and bed surface angle: 30-60°) (or = 11.76, 95% CI: 1 49-76.28) is the key points of cooperation for the successful implementation of bedside TCD in potential brain death patients. Conclusions: The targeted cooperation can ensure the successful implementation of bedside TCD judgment of brain death, and the results need further external validation.